Analisis Energi Panas Pada Proses Pengeringan Manisan Pepaya (Carica papaya l.) Menggunakan Alat Pengering Tipe Rak (Analysis of Thermal Energy in Candied Papaya (Carica papaya L.) Drying Process using Shelf Type Dryer): Analysis of Thermal Energy in Candied Papaya (Carica papaya L.) Drying Process using Shelf Type Dryer - Dwi Yulita; Murad Murad; Sukmawaty Sukmawaty (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2016)
Conventional drying still has many deficiencies; weather dependence is one of the problems. Therefore, alternative treatment needed to be conducted by using mechanical dryer that use heat and require additional energy for heating the material and vaporized the water, such as a shelf type dryer. This study aims to analyze thermal energy and studying energy balance in candied papaya drying process at shelf-type. This research was conducted at Laboratory of Bioprocess Engineering and Laboratory of Power and Machinery, in Studies Program of Agriculture Engineering, Faculty of Food and Agroindustrial Technology, University of Mataram. This study was performed using experimental design and energy equilibrium approach, with variable of air flowrates which varies at 3.43 m/sec and 4.55 m/sec. Amount of the outcoming energy obtained at 3.43 m/sec was 4477.12 to 4821.52 kJ/h and at 4.55 m/sec was 5437.80 kJ/h to 6797.25 kJ/h. While useful energy at 3.43 m/sec decreasing from 3675.37-1336.83 kJ/h and useful energy at 4.55 m/sec decreasing from 3891.71 kJ/h to 1082.45 kJ/h. The outcoming energy decreasing from 4926.06 kJ/h to 2292.07 kJ/h at3.43 m/sec and 5247.75 kJ/h to 2155.51 kJ/h at 4.55 m/sec.